Efeito biológico do Biodentine® e do MTA sobre exposição de tecido pulpar e periodontal da furca : estudo em ratos - Reis, Magda de Sousa (2015)
The aim of this study was to evaluate dental pulp and furcal periodontal tissue responses to mineral trioxide aggregate (MTA) and to a calcium silicate-based material (Biodentine™). The lower first molars in hundred forty (140) male Wistar rats were divided into groups according to the experimental site and period (14 and 21 days) testing two materials (n=8 per group/period in pulpotomy and n=6 per group/period in furcal perforation). Groups capped and sealed with MTA or Biodentine™ were restored with silver amalgam; in an additional test group, teeth were capped and restored with Biodentine™. Teeth capped with gutta-percha and restored with silver amalgam served as a positive control and untouched teeth were negative control. Histological evaluation of pulp responses and macroscopic examination of coronal sealing were performed. Inflammation extension and intensity, degenerative events and formation of mineralized tissue barrier were assessed. In the experiment of furcal perforations, inflammation extension and intensity, bone resorption and cement formation were assessed histologically. All results underwent ANOVA and Tukey post hoc tests (p<.05). In pulpotomy, Biodentine™ and MTA presented satisfactory results, which were characterized by a mild inflammatory response (p<.0001) and more pronounced formation of mineralized barrier (p<.0001) compared to teeth capped with gutta-percha. When used as a restorative material, Biodentine™ kept coronal sealing in only 37.5% of the samples. As to furcal perforations, Biodentine™ and MTA presented satisfactory results, which were characterized by a milder inflammatory response compared to the control, regardless of the material used for coronal sealing and of the experimental period evaluated (p<.0001). All test groups showed less bone resorption than the positive control after 21 days (p<.05), being this difference more pronounced in teeth restored with silver amalgam. Cement repair occurred in 30% of MTA and Biodentine™ samples, and was not detected in any specimen of the positive control group. In conclusion, Biodentine™ and MTA promoted similar responses when used to pulp capping and furcal perforation sealing. On the other hand, the use of Biodentine™ as temporary restorative material did not promote efficient coronal sealing. Although further investigations are required, Biodentine™ can be considered an alternative for pulpotomy and furcal perfuration.